Liberalisation and regulation of trade in the Southern African Development Community (SADC) : a critical analysis of the SADC trade protocol's provisions and its implementation - Dube, Memory (Rhodes University, Faculty of Law, Law, 2009)
The Southern African Development Community (SADC) declared a Free Trade Area on 17 August 2008. The Free Trade Area is the ultimate objective of the Trade Protocol on trade cooperation in SADC, signed in 1996. The Protocol is supported and complemented by the ambitious Regional Indicative Strategic Development Plan (RISDP). The idea behind the SADC Trade Protocol was to counter the developmental challenges facing SADC member states and to improve the productive and trade capacity of SADC countries. The implementation of the SADC Free Trade Area has been guided by the WTO/GATT regulatory framework on regional trade agreements, particularly GATT Article XXIV, the Understanding on the Interpretation of GATT Article XXIV, as well as the Decision on Differential and More Favourable Treatment, Reciprocity and Fuller Participation of Developing Countries (Enabling Clause). This research seeks to analyse the SADC Trade Protocol's provisions and the implementation of such provisions. To facilitate an understanding of factors that affect the implementation of the SADC Trade Protocol, SADC's institutional and operational framework is discussed from a legal-historical perspective. The provisions of the Trade Protocol are analysed for compliance with WTO/GA TT rules as well as for applicability within the SADC context. The provisions of the WTO/GA TT regulatory framework on regional trade agreements are also analysed with a view to determining whether they are applicable in developing country situations such as SADC. The Free Trade Area is seen as the first step towards regional economic integration in the region and is to be followed by a Customs Union, a Common Market and then eventually an Economic Community with its own central bank and regional currency. It is envisaged that the region will proceed through all these traditional theoretical phases of economic integration between 2008 and 2018. The implementation of the Trade Protocol has been beset with institutional, administrative and infrastructural challenges which pose obstacles to the attainment of the other stages of economic integration in the time frames prescribed in the RISDP. These challenges are assessed for impact on the regional economic integration of SADC by evaluating the progress towards implementing the Trade Protocol provisions and the implementation of measures taken towards the launch of the Free Trade Area. Emerging issues are also identified and analysed for their effect on the Free Trade Area and the general economic agenda of SADC. Of particular note is the Economic Partnership Agreements (EPAs) being negotiated with the European Union where SADC countries are negotiating in four different configurations. An analysis of this EPA situation reveals that it compounds a pre-existing problem: that of overlapping membership of regional trade agreements. Prior to the EPAs and the intensified drive towards the creation of the Customs Union, there was largely no need to rationalise the overlap in regional trade agreement memberships, but it is now a matter of urgency. The overlap in membership has complicated EPA negotiations and places serious doubts on the prospects of complete regional integration in SADC.This research concludes with observations on South Africa's complicated relationship with her SADC neighbours. South Africa's trade policies, as regards both the SADC region and the world, are discussed. Because of its political and economic dominance, South Africa's policies have a ripple effect on the rest of SADC; hence the need for South Africa to be vigilant in formulating and implementing its trade policies.
Keywords: General Agreement on Tariffs and Trade (Organization); World Trade Organization; Customs unions; Foreign trade regulation; Free trade -- Africa, Southern; Southern African Development Community International trade